Regenerative Endodontic Procedures in Immature Permanent Teeth With Dental Trauma: Current Approaches and Challenges - Zhou, Caixia; Yuan, Zhenglin; Xu, Hanxin; Wu, Linrui; Xie, Chun; Liu, Jiarong (Frontiers in Dental Medicine, 2022)
After dental trauma to immature permanent teeth (IPT) there can be pulpitis, necrotic and periapical periodontitis, which will halt further root development. Traditional endodontic root canal treatments and apexification cannot revitalize the necrotic pulp to revitalize the tooth to promote further root development. As a consequence, IPT with thin dentinal walls can be prone to fracture and if a fracture occurs, the patient will likely suffer a loss of the tooth. In an attempt to save IPT, there has been a growing interest among dentists to use regenerative endodontic procedures (REPs) to revitalize a replace dental pulp to continue root development and strengthen the dentinal walls to help prevent a subsequent loss of the tooth. However, the effectiveness of REPs and the precise methods to successfully accomplish REPs are controversial. Therefore, the objective of this review is to compare the different approaches to REPs in case reports by highlighting their advantages and limitations.